PERAN PERWAKILAN DIPLOMATIK DALAM PERLINDUNGAN PEKERJA MIGRAN INDONESIA DI MALAYSIA PASCA DITANDATANGANINYA MOU TENTANG ONE CHANNEL SYSTEM - Fitria, Yenni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Resolving conflicts between countries will rely on one of the national laws of a country in conflict, it feels unfair because the values that are embedded in each individual are definitely different. Protection is not only in the form of legal protection but also providing outreach and providing foreign language learning facilities. The protection referred to in the article above can be carried out by diplomatic representatives who are